Lanthanum Doped Strontium Titanate Nanomaterial for Photocatalytic and Supercapacitor Applications - Deshmukh, V.V.; Nagaswarupa, H.P.; Ravikumar, C.R.; Anil Kumar, M.R. Anil Kumar; Shekhar, T.R. Shashi; Ananda Murthy, H.C. (Asian Journal of Chemistry, 2020)
We report the synthesis of lanthanum doped strontium titanate (Sr1-xLaxTiO3,x=0.1) by sol-gel method. The physical properties of the as-synthesized sample were systematically studied through X-ray powder diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDAX). Diffraction peaks in XRD supported the cubic formation of perovskite-type crystal structure. The image analysis of nanomaterial by SEM and TEM techniques disclosed aggregates of nanoparticles with grain size about 20 nm. The study by UV-DRS exposed the band energy gaps (Eg) of 3.4 eV for strontium titanate nanoparticles, respectively. The degradation studies for three days were carried out for three dyes. Malachite green and rhodamine blue, strontium titanate nanoparticles showed utmost photocatalytic activity for rhodamine blue under UV light irradiation (from 0 to 80 min) as compared to malachite green. Properties of electrochemistry were looked into by cyclic voltammetry and galvanostatic charge/discharge in 1M KCl electrolyte. The Sr0.9La0.1TiO3 electrode displayed maximal specific capacitance of 306.74 F g-1 at current 1mA from galvanostatic charge-discharge curve. The rare earth doped perovskite Sr0.9La0.1TiO3 nanomaterial exhibited increased surface area with superior supercapacitance property.